Precedentes judiciais vinculantes e a sentença arbitral: aplicação cogente ou voluntária? - Toledo, José Eduardo Tellini (2022)
The proposed topic to be analyzed scientifically is the subordination, or not, of arbitrators to binding judicial precedents, when drafting an arbitration award, mainly because the current legal norm equates arbitrators to judges in fact and in law. In addition, it is proposed to know whether, in the ratification of a foreign arbitral award, the Superior Court of Justice is also subject to the application of these binding precedents. It is of great importance, not only because of the growth in the application of arbitration in various branches of law, but also because of the existence of bills aimed at the implementation of tax arbitration in Brazil (federal and state), which make it mandatory to observe these precedents. binding legal proceedings, under penalty of annulment of the arbitration award. It is known that the subject is controversial and will be the subject of much criticism. But all of them, whenever constructive, are welcome. In order to present a correct solution (according to the understanding I adopted), it is necessary to analyze the legal nature of the arbitration award and its relationship with the Brazilian legal system, especially when arbitrations are subject to Brazilian legislation. Starting from the evolution of the application of language in law, the correct concept of the legal norm, the analysis of the concept of system and where arbitration is included in it, the understanding of the so-called binding precedents, this study will demonstrate the relevance of the arbitration procedure and the award arbitration to the Brazilian legal system and, therefore, to binding judicial precedents. This study does not intend to exhaust the subject, since for that, there would be a need for a full and immutable knowledge on this subject, which we know is impossible. Furthermore, I know that each chapter of this thesis could become a new thesis, given the vastness of each subject. For this reason, and for methodological reasons, I intentionally chose to present the central theme of each theme mentioned in the respective chapter, necessary for the reader to follow the line of reasoning developed by me. I think it opportune to mention that this thesis was partially submitted to the academy through an article presented in a collection published on the occasion of the XVI National Congress of Tax Studies of the Brazilian Institute of Tax Studies (IBET) , so that discussions could be held, with the purpose of deepen the necessary knowledge which is described here